Two remarkable new species of webspinners in the genus Eosembia Ross, 2007 (Embioptera: Oligotomidae) from Thailand - Poolprasert, Pisit; Sitthicharoenchai, Duangkhae; Lekprayoon, Chariya; Butcher, Buntika Areekul (Zootaxa, 2011)
Two new species of webspinners (Embioptera) in the genus Eosembia Ross from Thailand, E. lamunae sp. n. and E. paradorni sp. n., are described and illustrated. These species bring the total number of species known from eastern, southeastern and southern Asia to 15 species. An identification key to the currently recognized species in the genus Eosembia, based on adult males, is included.